The Effect of Aqueous Extract of Pine Kindling on the Liver and Kidney Tissues of Diabetic Rats - Ökkeş,; Yılmaz, Okkes; Yilmaz,; Demır, Ersın; Sarıgül, Halise (My University, 2020)
In this study, the effect of aqueous extract of kindling wood obtained from pine trees on liver and kidney tissues of streptozotocin (STZ)-induced diabetic rats was investigated. Male Sprague Dawley rats were divided into five groups: 1) Control,2) STZ rats 3) STZ rats treated with aqueous extract obtained from kindling wood of pine trees (respectively 100 g/L, 200g/L and 400 g/L) for 10 weeks. According to our results, it was determined that this extract showed beneficial effects onoxidative stress (Malondialdehyde (MDA), Reduced glutathione (GSH), Oxidized glutathione (GSSG)) in liver and kidney tissues. Pine kindling extract showed generally positive effects on glycogen, cholesterol, alpha tocopherol, retinol, palmitic acid,stearic acid, oleic acid, linoleic acid, arachidonic acid and docosahexaenoic acid parameters in the liver and kidney tissuesof diabetic rats. Pine kindling extract did not showed inhibitory effect on the amylase enzyme activity derived from bovine,porcine pancreas, fungi and bacteria during in vitro experiments. Pine kindling extract also did not exhibit inhibitor effecton ?-glycosidase enzyme that hydrolyzes disaccharides
Keywords: Beslenme ve Diyetetik; Genel ve Dahili Tıp; Kimya; Tıbbi; Biyokimya ve Moleküler Biyoloji